PRAKTIK DISTRIBUSI ZAKAT KONSUMTIF TRADISONAL DI KARANG PENANG SAMPANG - Harisah Harisah; Zainulloh Zainulloh (LP2M IAI Miftahul Ulum Pamekasan, 2019)
(The position of zakat in economics of islam is very important, not only as part of the pillars of islam, but also as an indicator of economic development in Islam. Through zakat distribution will be conveyed to those who are entitled. However, the development of increasingly modern economics requires economic actors to be more sensitive to look at situation as well and for the distribution of zakat which should not always be consumptive as like district of karang Penang Sampang but more than it, the productive distribution of zakat will be able become one of the methods of economic development by making zakat funds as capital in growing up the community’s economy. Based on discussion are two problems which become the principle for this research, they are how a strategy the distribution of zakat in district of karang penang and how the positive impact for the choosen strategy. The researcher used a qualitative approach method with a type of field research in this research. The data obtained from interviews, observation to location, and making documentation. The result of research are, for the first is the distribution of zakat with traditional comsumptive strategy and The second is The positive impact for the distribution of zakat as just fullfil needs can not be developed to become productive funds and develop the community’s economic).